Assessment of the predictive factors in body image of Iranian patients with breast cancer: Demographic factors - Hojjat Torkmandi; Mojgan Firouzbakht; Amir Hossein Goudarzian; Ameneh Yaghoobzadeh; Hamid Sharif Nia; Mobin Mohammadinezhad (Zanjan University of Medical Sciences and Health Services, 2020)
Background: Changes of body image following breast cancer is one of the factors affecting the quality of life of women with this disease. Objectives: Thus, the factors affecting the body image need to be identified to improve their quality of life. Therefore, this study aimed to investigate the factors affecting the body image in Iranian women diagnosed with breast cancer. Methods: In this cross-sectional study, 200 breast cancer women were participated using convenience sampling method during April to January, 2018. The data were collected using a demographic questionnaire and body image questionnaires after breast cancer (BIBCQ). The data were analyzed using Univariate and Multivariate linear regression in SPSS25 at a significance level of 0.05. Results: The mean age of participants was 48.43 (SD=10.53). The results showed that the variables such as type of treatment (p=0.002), physical health (β=-0.49, p<0.001), economic status (β=-0.62, p<0.001), and quality of life (β=-0.41, p=0.003) had the predictability potential of the body image in those under mastectomy. Educational level (β= 0.22, p=0.02) and physical health (β=-0.25, p=0.01) factors could predict body image in people with no mastectomy. Conclusion: The results of the study indicated that the improvement of the economic status has a positive effect on the body image of breast cancer. In addition, this factor can improve the quality of life in women who survive breast cancer.